Range, sexual dimorphism and bilateral asymmetry of rostral tooth counts in the smalltooth sawfish Pristis pectinata Latham (Chondrichthyes: Pristidae) of the southeastern United States - Wiley, Tonya R.; Simpfendorfer, Colin A.; Faria, Vicente V.; Mcdavitt, Matthew T. (Zootaxa, 2008)
Rostral tooth counts of Pristis pectinata specimens from museum collections, research surveys, and fisheries activities were examined to provide information on sexual dimorphism, bilateral asymmetry, and to aid in the resolution of the taxonomic uncertainty that surrounds the Pristidae. Counts were taken from 105 smalltooth sawfish captured in Florida and Georgia, USA, from 1834 to 2007. The number of rostral teeth present was 22 to 29 per side and 45 to 56 in total. These counts were more constrained, and mean values lower, than historically reported for this species in the literature. Pristis pectinata rostral tooth counts exhibited sexual dimorphism, with males on average having more rostral teeth than females. Bilateral asymmetry in rostral tooth counts was displayed in 73% of individuals, with no consistent side on which the greatest count occurred. No significant difference between left and right side rostral tooth counts was found.